2015
DOI: 10.1371/journal.pone.0129625
|View full text |Cite
|
Sign up to set email alerts
|

Specific Intensity Direct Current (DC) Electric Field Improves Neural Stem Cell Migration and Enhances Differentiation towards βIII-Tubulin+ Neurons

Abstract: Control of stem cell migration and differentiation is vital for efficient stem cell therapy. Literature reporting electric field–guided migration and differentiation is emerging. However, it is unknown if a field that causes cell migration is also capable of guiding cell differentiation—and the mechanisms for these processes remain unclear. Here, we report that a 115 V/m direct current (DC) electric field can induce directional migration of neural precursor cells (NPCs). Whole cell patching revealed that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 56 publications
(65 reference statements)
4
45
0
Order By: Relevance
“…In the context of neurogenesis, neuromodulation is gaining traction as a reparative tool for brain injury and disease 118,134 . Neurostimulation stimulates neural progenitor proliferation 135137 , directs the migration (galvanotaxis) of neuronal and glial precursors 134,138140 and promotes their differentiation 136,137,140,141 . Interestingly, tDCS-polarized proinflammatory microglia accompany NG2-precursor migration to promote functional recovery after stroke 130 .…”
Section: Glial-activation Challenges and Design Considerationsmentioning
confidence: 99%
“…In the context of neurogenesis, neuromodulation is gaining traction as a reparative tool for brain injury and disease 118,134 . Neurostimulation stimulates neural progenitor proliferation 135137 , directs the migration (galvanotaxis) of neuronal and glial precursors 134,138140 and promotes their differentiation 136,137,140,141 . Interestingly, tDCS-polarized proinflammatory microglia accompany NG2-precursor migration to promote functional recovery after stroke 130 .…”
Section: Glial-activation Challenges and Design Considerationsmentioning
confidence: 99%
“…; Zhao et al . , ), which corresponds to an EF strength of about 5 V/cm in vitro . Wounding the corneal epithelium disrupts tight junctions among the cells that normally help maintain the potential difference.…”
Section: Discussionmentioning
confidence: 97%
“…Our experimental results are in agreement with the literature (Hammerick et al 2010b). Many ª 2017 Japanese Society of Developmental Biologists studies have confirmed that a 50 lm of mammalian corneal epithelium exhibits approximately 25 mV transepithelial potential difference across (Hammerick et al 2010b;Zhao et al 2011Zhao et al , 2015, which corresponds to an EF strength of about 5 V/cm in vitro. Wounding the corneal epithelium disrupts tight junctions among the cells that normally help maintain the potential difference.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations